Putting it down to experience: ageing and the subject in Sartre, Munro and Coetzee. (2nd January 2018) - Barry, Elizabeth
Abstract: This article will consider the kind of experience represented by old age, and whether we learn through this experience, or whether it falls outside our capacity or inclination to theorise and understand. It will look at ageing, and in particular ageing for women, through the lens of Sartrean philosophy – in relation to Sartre's scepticism about gaining knowledge or character through simply living longer, and in relation to his position (endorsed by Simone de Beauvoir) that the body is no more than a necessary obstacle that might hamper our efforts to grasp the world (especially if we are women). In the light of the reflections on ageing and gender in Sartre and Beauvoir's thought, it will use Margaret Morganroth Gullette's model of the 'midlife progress narrative' to consider experience, knowledge and character in female ageing in the fiction of Alice Munro ('Lichen' [1985] and 'Hold Me Fast, Don't Let Me Pass' [1988]) and J.M. Coetzee ( Elizabeth Costello [1999]).